Problem-Based Learning Technology (Journal of Pedagogical Inventions and Practices, 2023)
Problem-based learning is one of the goals of a creative, active person. This article discusses about today’s effective teaching technology – problem-based learning, its essence and an important aspect of organizing and conducting problem-based learning